2018
DOI: 10.1097/md.0000000000009943
|View full text |Cite
|
Sign up to set email alerts
|

“Living High-Training Low” improved weight loss and glucagon-like peptide-1 level in a 4-week weight loss program in adolescents with obesity

Abstract: Background:“Living High-Training Low” (LHTL) is effective for the improvement of athletic ability; however, little is known about the effect of LHTL on obese individuals. The present study determined whether LHTL would have favorable influence on body composition, rebalance the appetite hormones, and explore the underlying mechanism.Methods:Adolescents with obesity [body mass index (BMI) >30 kg/m2] were randomly assigned to “Living Low-Training Low” (LLTL, n = 19) group that slept in a normobaric normoxia cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
(53 reference statements)
1
19
0
1
Order By: Relevance
“…4,92 Following these initial observations, several recent studies compared the effect of exercise training in hypoxia versus normoxia in individuals with obesity. Greater improvement in body weight or composition was observed following hypoxic training in some [93][94][95][96] but not all studies, 23,[97][98][99][100][101] Yang et al 102 in adolescents with obesity used a "living hightraining low" strategy similar to athletes (i.e., sleeping in a hypoxic room and training in normoxia) 44 did not appear to significantly improve blood lipid status. 90,91,96,[99][100][101][102] Some 94,103 but not all 23,91,95,97,101,104 studies reported a reduction in blood pressure following hypoxic exercise training compared with normoxic exercise training.…”
Section: Hypoxia As Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4,92 Following these initial observations, several recent studies compared the effect of exercise training in hypoxia versus normoxia in individuals with obesity. Greater improvement in body weight or composition was observed following hypoxic training in some [93][94][95][96] but not all studies, 23,[97][98][99][100][101] Yang et al 102 in adolescents with obesity used a "living hightraining low" strategy similar to athletes (i.e., sleeping in a hypoxic room and training in normoxia) 44 did not appear to significantly improve blood lipid status. 90,91,96,[99][100][101][102] Some 94,103 but not all 23,91,95,97,101,104 studies reported a reduction in blood pressure following hypoxic exercise training compared with normoxic exercise training.…”
Section: Hypoxia As Treatmentmentioning
confidence: 99%
“…Greater improvement in body weight or composition was observed following hypoxic training in some [93][94][95][96] but not all studies, 23,[97][98][99][100][101] Yang et al 102 in adolescents with obesity used a "living hightraining low" strategy similar to athletes (i.e., sleeping in a hypoxic room and training in normoxia) 44 did not appear to significantly improve blood lipid status. 90,91,96,[99][100][101][102] Some 94,103 but not all 23,91,95,97,101,104 studies reported a reduction in blood pressure following hypoxic exercise training compared with normoxic exercise training. Similarly, only two 99,101 out of six studies 23,91,[97][98][99]101 that investigated exercise performance following hypoxic exercise training in individuals with obesity reported greater improvement compared with normoxic exercise training.…”
Section: Hypoxia As Treatmentmentioning
confidence: 99%
“…It was reported that 4 weeks of a low-calorie diet plus exercise 6 h/week in 3000 m normobaric hypoxic conditions in addition to exercise 16 h/week in normoxic conditions led to significantly more weight loss than that observed in the normoxic group (− 7.0% versus − 4.2%) [21]. LHTL also reduced more body weight in Yang's report [42]. In our study, the daily energy intake met the resting metabolic needs which is 3-to 4-fold higher than that used in Kong's research [21]; however, more weight loss was observed.…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have shown that hypoxic training can reduce body weight and body fat in humans and rodents ( Ji et al, 2017 ; Camacho-Cardenosa et al, 2018a ; Yang et al, 2018 ; Park et al, 2019 ; Wang et al, 2019 ). This effect might be due to hypoxic exercise leading to the suppression of appetite ( Matu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%